Hemorrhagic and procoagulant P-III snake venom metalloproteinases differ in their binding to the microvasculature of mouse cremaster muscle - Herrera Arias, Cristina (2020)
Binding of two P-III snake venom metalloproteinase (SVMPs), one procoagulant and one hemorrhagic, to microvessels was compared in an ex vivo model. The procoagulant SVMP did not bind to the microvasculature, in contrast to the clear localization on microvessels of the hemorrhagic SVMP. Deglycosylation of the procoagulant enzyme did not enable this toxin to bind to microvessels, suggesting that glycosylation is not interfering with binding. These observations suggest that procoagulant SVMPs lack exosites for interaction with microvessels components.